(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
In this paper, we report the amalgamation of another ligand phthalicacid[bis(benzyloxy)ethyl] ester by the response of phthalic anhydride and ethylene glycol. The ligand was portrayed by FTIR, HNMR and Mass spectra. Binuclear Copper (II) complex of the ligand bound to four acetic acid derivation particles was orchestrated and described by electronic spectra, FTIR spectra, EPR spectra, thermo gravimetric (TGA) investigation and electrochemical examinations. The superoxide rummaging action of the complex is additionally announced.